Peran Aparatur Desa Dalam Pemberdayaan Kelompok Tani Di Desa Ujong Blang Kecamatan Kuala Kabupaten Bireuen Tahun 2022 - Jahidin, Taufik (LPPM Universitas Almuslim, 2024)
Empowerment of farmer groups in Ujong Blang Village, Kuala District, Bireuen Regency has not been implemented optimally. This can be seen from the economic powerlessness of farmers which is exacerbated by the low level of village apparatus participation. The purpose of this study was to describe the role of village apparatus in community empowerment in Ujong Blang Village, Kuala District, Bireuen Regency. In this study using a descriptive qualitative research method which aims to describe and analyze a problem in order to obtain an overall picture that is described in words or sentences in the final results of the study. The role of village apparatus in empowering farmer groups in Ujong Blang Village, Kuala District, Bireuen Regency has not been maximized, so it has not made any changes to reducing poverty, increasing income, increasing productivity, increasing ability to manage farming and increasing welfare. Capital assistance, subsidized fertilizers and superior seeds provided by the Government have not been received equally by farmer groups. Counseling and mentoring from Village Officials has also not been carried out effectively, the availability of the facilities needed by farmers is inadequate and there is no institution that can distribute agricultural tools and accommodate harvests from farmers. Obstacles in empowering farmer groups in Ujong Blang Village, Kuala District, Bireuen Regency are the low knowledge of farmers, where most farmers have only elementary and junior high school education, the weakness of agricultural extension programs so that they are unable to reach their targets for poor farmers, the limited role of the government in providing production inputs such as assistance capital, quality seeds and subsidized fertilizers, lack of concern and seriousness of members of farmer groups in participating in counseling and the lack of extension staff resources as trainers and educators.